2016
DOI: 10.1002/star.201500316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion factors and particle size on starch properties of nixtamalized whole blue corn snacks

Abstract: The aim of this study, was to evaluate the effect of extrusion conditions and particle size index on the starch properties of expanded nixtamalized snacks elaborated with whole blue corn. Whole grains were ground to achieve two different particle size indexes (PSI), 83.9 and 94.1, and were extruded at three feed moistures (14, 16.5, and 20.5%). The data suggested that the severity of milling and the extrusion process resulted in higher starch degradation, specifically in the snacks obtained with a feed moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…A similar effect was observed in yam (Ipomoea batatas) flours from Hebei (China), and the starch percentages obtained (43.58%), similar to those of the present work, presented a particle size of 355 µm; however, with particle size 75 µm, these authors obtained a somewhat higher content of starch (61.90%) [44]. The increase in starch with smaller particle sizes is attributed to the breakage of the flour structure so more active sites are exposed for enzymatic degradation [45]. In parallel, it has also been observed that the sugar content may increase slightly for the finest particle sizes, while decreasing for medium and coarse particle sizes, attributing this fact to the hydrolysis of starch into oligosaccharides and monosaccharides in the flour [44].…”
Section: Moisturesupporting
confidence: 87%
“…A similar effect was observed in yam (Ipomoea batatas) flours from Hebei (China), and the starch percentages obtained (43.58%), similar to those of the present work, presented a particle size of 355 µm; however, with particle size 75 µm, these authors obtained a somewhat higher content of starch (61.90%) [44]. The increase in starch with smaller particle sizes is attributed to the breakage of the flour structure so more active sites are exposed for enzymatic degradation [45]. In parallel, it has also been observed that the sugar content may increase slightly for the finest particle sizes, while decreasing for medium and coarse particle sizes, attributing this fact to the hydrolysis of starch into oligosaccharides and monosaccharides in the flour [44].…”
Section: Moisturesupporting
confidence: 87%
“…Starch contents of orange and purple‐fleshed SPF increased with decreasing particle size, which increased to 55.19 and 61.90 g/100 g DW at particle size 75 μm, respectively. The increment of starch due to the grinding process that breakdown the molecular structure of flour and exposes more enzymatic active sites during starch degradation, resulting in a higher amount of starch quantified (Escalante‐Aburto et al., 2016). The starch content ranges in the current study were consistent with the previous report (Cartier et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The dispersed solution was stirred with a plastic paddle, and a heating cycle was started at a controlled rate (50° C–90 °C–50 °C). The maximum viscosity, final viscosity, retention force, breakdown, and setback in cP were analyzed, and the rheological behavior was analyzed using a Rapid Visco Analyser (model RVA-3D, Newport Scientific, Warriewood, Australia) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%